Defense-Related Transcriptional Reprogramming in Vitamin E-Deficient Arabidopsis Mutants Exposed to Contrasting Phosphate Availability - Allu, Annapurna D.; Simancas, Bárbara; Balazadeh, Salma; Munné-Bosch, Sergi (Frontiers in Plant Science, 2017)
Vitamin E inhibits the propagation of lipid peroxidation and helps protecting photosystem II from photoinhibition, but little is known about its possible role in plant response to Pi availability. Here, we aimed at examining the effect of vitamin E deficiency in Arabidopsis thaliana vte mutants on phytohormone contents and the expression of transcription factors in plants exposed to contrasting Pi availability. Plants were subjected to two doses of Pi, either unprimed (controls) or previously exposed to low Pi (primed). In the wild type, alpha-tocopherol contents increased significantly in response to repeated periods of low Pi, which was paralleled by increased growth, indicative of a priming effect. This growth-stimulating effect was however abolished in vte mutants. Hormonal profiling revealed significant effects of Pi availability, priming and genotype on the contents of jasmonates and salicylates; remarkably, vte mutants showed enhanced accumulation of both hormones under low Pi. Furthermore, expression profiling of 1,880 transcription factors by qRT-PCR revealed a pronounced effect of priming on the transcript levels of 45 transcription factors mainly associated with growth and stress in wild-type plants in response to low Pi availability; while distinct differences in the transcriptional response were detected in vte mutants. We conclude that alpha-tocopherol plays a major role in the response of plants to Pi availability not only by protecting plants from photo-oxidative stress, but also by exerting a control over growth- and defense-related transcriptional reprogramming and hormonal modulation.